The physiology of contemporary Olympic cross-country mountain biking: A systematic review - Protzen, G.; Inoue, A.; Buzzachera, C.; Doma, K.; Devantier-Thomas, B.; Herrero-Molleda, A.; García-López, J.; Boullosa, D. (Sports Medicine - Open, 2026)
Background Olympic Cross-Country (XCO) mountain biking has evolved since its 1996 Olympic debut, with races becoming up to 40% shorter and more technically demanding. These changes may have altered the physiological demands, challenging the applicability of earlier evidence. This systematic review examines the physiology of contemporary XCO, focusing on athletes` characteristics, race demands, and training interventions.